EXPERIMENTAL AND TEXTURE-DERIVED P-WAVE ANISOTROPY OF PRINCIPAL ROCKS FROM THE TRANSALP TRAVERSE: AN AID FOR THE INTERPRETATION OF SEISMIC FIELD DATA - Ullemeyer K.; Behrmann J.H.; Siegesmund S.; Rasolofosaon P.N.J. (My University, 2006)
A representative suite of deformed, metamorphic rocks from the TRANSALP reflection seismic traverse in the Eastern Alps was studied in the laboratory with respect to elastic properties and whole-rock texture. Compressional wave (P-wave) velocities and their anisotropies were measured at various experimental conditions (dry, wet, confining pressure), and compared to the texture-related component of anisotropy. Here ‘texture’ refers to crystallographic preferred orientations (CPOs), which were determined by neutron texture goniometry. In gneisses and schists P-wave anisotropies are mainly controlled by the microcrack fabric. In marbles and amphibolites CPO contributes very significantly to anisotropy. At 200 MPa confining pressure the degree of anisotropy is between 5% and 15%, depending on rock composition and/or CPO intensity. Special emphasis was also put on discussing possible effects of fluids on seismic velocity and anisotropy. Distributions of water-filled microcracks and pores are distinctly anisotropic, with maximum contribution to bulk rock velocity mostly parallel to the foliation pole. Decreasing P-wave velocity and increasing anisotropy of immersed samples may be explained by crack-induced changes of the elastic moduli of bulk rock. The main conclusion regarding interpretation of TRANSALP data is that strong reflections in the deep Alpine crust are probably due to marble–gneiss and metabasite–gneiss contacts, although P-wave anisotropy and boundaries between zones of ‘dry’ or ‘wet’ series may contribute to reflectivity to some extent.